Hybrid brayton multi-stage concentrated solar power plant energy and exergy performance study (2021)
Hybrid Brayton concentrated solar power (CSP) plants have been gaining attention in the last decade upon many advantages regarding the use of traditional generation technologies combined with renewable energy sources. However, some technical and economic issues must be solved to allow its widespread use. Research and development efforts are deemed essential to the study of factors that constrain cycle performance looking to increase its efficiency, reducing fuel consumption, and decreasing emissions. This study presents the performance evaluation of a hybrid multi-stage CSP plant considering specific environmental conditions to attain the factor that constrains its optimal performance. Overall energy and exergy plant efficiencies are analyzed, considering an arbitrary number of stages. For instance, a double compression expansion hybrid CSP plant shows the overall energy efficiency of 32% larger, a 30% higher exergy efficiency, and a fuel conversion rate around 18% larger when compared with a single-stage CSP plant.